Numerical Simulation Study on the Layered Phenomenon of Lakes and Reservoirs Destroyed by a Forced Circulation Device - Jiaxing Xu; Minghan Luo; Dema Ba; Gongde Wu; Ligang Xu; Taeseop Jeong (Journal of Marine Science and Engineering, 2022)
Thermal stratification is a common phenomenon in lakes and reservoirs. It has a significant influence on water quality dynamics. The destruction of the thermal stratification of lakes and reservoirs can affect the water environment, improve the water quality and the water environment quality and prevent the occurrence of eutrophication. In this study, computational fluid dynamics (CFD) combined with a Eulerian two-phase flow model is used to predict the damage caused by an airlift device to the thermal stratification phenomenon of lake water. The results show that the two devices with different sizes can contribute to a certain exchange of kinetic and thermal energy, affecting the liquid velocity and temperature in the lake water under the condition of different gas velocities. Furthermore, the degree of damage to the thermal stratification phenomenon of lake reservoir is small. However, with the same gas velocity, the device with a guide plate can have a greater impact on the liquid velocity and temperature in the lake water. Further prediction results show that the airlift installed with a guide plate can affect the heat transfer of liquid in the lake and reservoir better and destroy the thermal stratification phenomenon effectively. The quantitative results of model prediction can provide an effective basis for future field scale-up experiments.